Examining the Psychosocial Factors of Mental Health Well-being Among Medical University Students: Gender-based Analyses - Yao, Geng; Jamal, Aziz; Abdullah, Mohd Zulkifli; Dzulkipli, Mohd Redhuan; Jamil, Nurizzati (Information Management and Business Review, 2024)
The mental health of university students is a major concern due to the various stressors they face, including academic pressures, social dynamics, and personal development challenges. Previous studies have shown that gender differences significantly impact how students perceive and express psychological distress. This study aimed to identify these differences in the context of academic stress, social support, self-esteem, academic motivation, and family functioning, and their association with psychological distress. The study involved 2206 medical students in a cross-sectional study at a medical university in Ningxia, western China. The data analysis revealed significant gender differences in scores for academic stress, social support, and academic motivation. Academic stress, social support, and family functioning were found to be significantly associated with psychological distress for both genders. However, academic motivation was found to significantly influence psychological distress only among male students, while self-esteem had an impact on female students. These findings highlight the need for tailored mental health services in universities to address gender-specific needs, such as providing counseling services that focus on coping with academic stress and strengthening social and familial support networks to improve student well-being.